Health Project Prioritization in Meta, Colombia, Using Anp-Dematel - Astrid León-Camargo; Seydyss Garay-Rodríguez (Applied Sciences, 2025)
The prioritization of healthcare projects in Colombia’s Meta Department was conducted using an integrated decision-making model that combines the Analytic Network Process and the Decision-Making Trial and Evaluation Laboratory. This multicriteria approach systematically evaluates interdependencies among strategic criteria while incorporating expert judgments to improve resource allocation and promote equity and accessibility in health services. The analysis identified the reconstruction of the healthcare center in Puerto Gaitán as the highest-priority intervention, followed by the expansion of the municipal hospital in Acacías and the establishment of an emergency regulation center. The results demonstrated a strong correlation between infrastructure development and the reduction of populations with unmet basic needs, emphasizing the crucial role of physical infrastructure in advancing health equity. Sensitivity analysis confirmed the robustness of the model under varying parameters. The integrated methodology proved particularly valuable for capturing complex interrelationships among criteria, balancing technical and equity considerations, and supporting transparent, evidence-based decisions for health investment planning in regional contexts that require both immediate responses and long-term system strengthening.